Assessment for University Classroom Climate Improvement in Indonesia - Hadiyanto Hadiyanto; Cepi Safrudin Abd Jabar; Sunu Trihantoyo; Zulaikha Zulaikha; Sari Febrianti (Universitas Negeri Padang, 2023)
Improving classroom climate is an effort to enhance the quality of education on a micro scale that needs to be encouraged for lecturers in tertiary education. Several tertiary classroom climate instruments have been developed in English, for example the Colleges and Universities Classroom Environment Inventory (CUCEI), What is Happening in this Class (WIHIC), and have been translated into several languages. The University Classroom Climate Inventory (UCCI) is a classroom climate instrument which was developed and adapted in Bahasa Indonesia based on the English classroom climate instrument. To obtain information about a conducive classroom climate in Indonesia, it is necessary to assess the difference between actual and preferred classroom climate in some universities. The sample of the study was 400 students of Universitas Negeri Padang, Universitas Negeri Yogyakarta, Universitas Negeri Surabaya, Universitas Negeri Jakarta, Public Islamic University of Sutan Syarif Kasim Pekanbaru, and Public Islamic Institute of Kerinci, Indonesia. The result of the study shows that there was a significant difference between the actual and the preferred climate, which mean that there is a need to make better classroom climate in for these universities.